Peripheral Artery Disease and Buerger-Allen Exercise - Sasikumar, Salini; George, Jomet (Innovational: Journal of Nursing and Healthcare, 2024)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by high blood sugar levels resulting from the body’s inability to produce or effectively use insulin. It can lead to various complications, including peripheral artery disease (PAD). PAD is a condition characterized by the narrowing or blockage of arteries that supply blood to the limbs, typically the legs. Exercise plays a crucial role in managing both DM and PAD. Buerger-Allen exercises (BAEs), also known as lower extremity exercises, are specific exercises designed to improve circulation in the legs and feet. These exercises are particularly beneficial for individuals with PAD, as they help increase blood flow to the affected limbs, reduce symptoms, and improve overall cardiovascular fitness. BAE has the following steps elevating the legs, pumping the feet, rotating the ankles, bending the knees, and lowering the legs. The exercise starts by elevating the legs to a level above the heart. This position helps to reduce swelling and improve blood flow. These exercises are typically performed in a controlled manner, with multiple repetitions of each movement. The frequency and duration of BAEs may vary based on an individual’s condition and their healthcare provider’s recommendations. It is essential to consult a healthcare professional before starting any exercise regimen, especially if the patient has DM or PAD, to ensure that the exercises are safe and suitable for your specific situation. Many research studies proved that BAE is very effective in reducing PAD among DM patients.